2012
DOI: 10.1111/fwb.12023
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of shredders on microbial biomass and decomposition in stream microcosms

Abstract: Summary 1. Animals play a major role in nutrient cycling via excretory processes. Although the positive indirect effects of grazers on periphytic algae are well understood, little is known about top‐down effects on decomposers of shredders living on leaf litter. 2. Nutrient cycling by shredders in oligotrophic forest streams may be important for the microbial‐detritus compartment at very small spatial scales (i.e. within the leaf packs in which shredders feed). We hypothesised that insect excretion may cause l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The presence of invertebrates enhanced the response of fungal biomass and also leaf mass loss. Invertebrate excretion can stimulate fungal biomass by increasing ammonia concentration in leaf substrata (Villanueva, Albariño, & Canhoto, 2012). These results are consistent with those obtained in the live treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of invertebrates enhanced the response of fungal biomass and also leaf mass loss. Invertebrate excretion can stimulate fungal biomass by increasing ammonia concentration in leaf substrata (Villanueva, Albariño, & Canhoto, 2012). These results are consistent with those obtained in the live treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The main function of shredders is the breakdown of large particles of plant material into smaller pieces that are then transported downstream or available to other stream consumers (Wallace & Webster, 1996). Shredders also make nutrients available to microbial consumers (Díaz Villanueva et al, 2012). In general, we refer to them as consumers of coarse particulate organic matter (CPOM) and producers of fine particulate organic matter (FPOM).…”
Section: Functional Feeding Groupsmentioning
confidence: 99%
“…Grazing by macroinvertebrates is also beneficial to microbes, as they recycle nutrients back into the environment (Vanni, 2002). As primary consumers in aquatic food webs, macroinvertebrates represent an important link between basal resources (e.g., algae and detritus) and upper trophic levels (e.g., fish) or microbial communities (Díaz Villanueva, Albariño & Canhoto, 2012). However, their role is not only to make energy available to upper trophic levels, they also regulate energy flow along the aquatic food web (Chew, 1974;Wallace & Webster, 1996).…”
mentioning
confidence: 99%
“…The opposite, that is stimulation of fungal growth and sporulation in the presence of shredders, was observed on recalcitrant substrata (Gonçalves et al ., ). This has been attributed to ammonium excreted by invertebrates (Villanueva, Albariño & Canhoto, ). Other authors reported no changes in fungal biomass, sporulation rates and community composition in the presence of shredders (Ferreira & Graça, ; Chung & Suberkropp, ).…”
Section: Introductionmentioning
confidence: 99%